Kajian Keruangan Penempatan Lokasi Masjid Agung Cipaganti di Kawasan Permukiman Kolonial Belanda Bandung - Santika, Denny (UIN SIber Syekh Nurjati Cirebon, 2025)
The Cipaganti Grand Mosque is located in the Cipaganti area of North Bandung. It was designed by Prof. Ir. C.P. Wolff Schoemaker and established in 1933, during the period when Bandung was designated as a gemeente (between 1906–1940). This study aims to explore the background behind the location of the Cipaganti Grand Mosque within a Dutch Colonial residential area and to understand the mosque’s status. This is important in order to identify patterns in the placement of places of worship/mosques in colonial settlements, as well as the relationship between the Cipaganti Grand Mosque and the local community in the colonial residential area, and with other religious buildings in the Cipaganti area. The study focuses on spatial aspects at a semi-micro/meso scale, using a descriptive-analytical method and inductive reasoning. The core idea of this research identifies three factors that influenced the location of the Cipaganti Grand Mosque. First, the establishment of the mosque within a Dutch Colonial residential area was influenced by the ethical policy and association policy. Second, it served to meet the religious needs of the Muslim community living in the Cipaganti area. Third, it functioned as a supporting facility for worship for employees working in near by institutions or agencies.Keywords: Mosque, Colonial Settlement, Meso/Semi-micro Scale Space, Gemeente, Background of Position, Status, Bandung.Abstrak: Masjid Agung Cipaganti terletak di kawasan Cipaganti Bandung Utara yang dirancang oleh Prof. Ir. C.P. Wolff Schoemaker dan didirikan pada tahun 1933 ketika Kota Bandung menjadi gemeente (antara tahun 1906-1940). Penelitian ini bermaksud untuk menjawab apakah yang melatarbelakangi letak Masjid Agung Cipaganti pada Pemukiman Kolonial Belanda dan bagaimana status masjid tersebut. Hal ini penting untuk mengidentifikasi pola penempatan tempat ibadah/masjid di permukiman kolonial, hubungan Masjid Agung Cipaganti dengan masyarakat di permukiman kolonial dan dengan bangunan keagamaan lainnya di kawasan Cipaganti. Kajian dalam penelitian ini berkaitan dengan aspek spasial skala semi mikro/meso dengan metode deskriptif analitis dan alur penalaran induktif. Inti gagasan dari penelitian ini terdapat tiga faktor yang melatarbelakangi keletakan Masid Agung Cipaganti. Pertama, berdirinya masjid ini di Permukiman Kolonial Belanda dipengaruhi kebijakan politik etis dan asosiasi. Kedua, untuk memfasilitasi kebutuhan ibadah masyarakat muslim yang bermukim di kawasan Cipaganti. Ketiga, sebagai fasilitas pendukung ibadah bagi para pekerja di instansi atau lembaga yang berdekatan dengan masjid.